Beneficial Effect of Systemic Allogeneic Adipose Derived Mesenchymal Cells on the Clinical, Inflammatory and Immunologic Status of a Patient With Recessive Dystrophic Epidermolysis Bullosa: A Case Report - Maseda, Rocío; Martínez-Santamaría, Lucía; Sacedón, Rosa; Butta, Nora; Arriba, María del Carmen de; García-Barcenilla, Sara; García, Marta; Illera, Nuria; Pérez-Conde, Isabel; Carretero, Marta; Jiménez, Eva; Melen, Gustavo; et al. (Frontiers in Medicine, 2020)
Recessive dystrophic epidermolysis bullosa (RDEB) is an incurable inherited mucocutaneous fragility disorder characterized by recurrent blisters, erosions and wounds. Continuous blistering triggers overlapping cycles of never-ending healing and scarring commonly evolving to chronic systemic inflammation and fibrosis. The systemic treatment with allogeneic mesenchymal cells (MSC) from bone marrow has previously shown benefits in RDEB. MSC from adipose tissue (ADMSC) are easier to isolate. This is the first report on the use of systemic allogeneic ADMSC, correlating the clinical, inflammatory and immunologic outcomes in RDEB indicating long-lasting benefits. We present the case of an RDEB patient harboring heterozygous biallelic COL7A1 gene mutations and with a diminished expression of C7. The patient presented with long-lasting refractory and painful oral ulcers distressing her quality of life. Histamine receptor antagonists, opioid analgesics, proton-pump inhibitors and low-dose tricyclic antidepressants barely improved gastric symptoms, pain and pruritus. Concomitantly, allogeneic ADMSC were provided as 3 separate intravenous injections of 106 cells/kg every 21 days. ADMSC treatment was well tolerated. Improvements in wound healing, itch, pain and quality of life were observed, maximally at 6-9 months post-treatment, with the relief of symptoms still noticeable for up to 2 years. Remarkably, significant modifications in PBL participating in both the innate and adaptive responses, alongside regulation of levels of profibrotic factors, MCP-1/CCL2 and TGF-β, correlated with the health improvement. This treatment might represent an alternative for non-responding patients to conventional management. It seems critical to elucidate the paracrine modulation of the immune system by MSC for their rational use in regenerative/immunoregulatory therapies.